Wisława Szymborska we Włoszech. Studium przypadku literackiego sukcesu - Światłowska, Agnieszka (Acta Neophilologica, 2024)
The article analyzes the phenomenon of Wisława Szymborska’s literary success in Italy, with a particular focus on the reasons behind her extraordinary popularity in the country. Despite her initial limited recognition, the poet gained the status of the most widely read in Italy, surpassing even local authors. The paper illustrates how Pietro Marchesani’s translations, the support of Italian Polish studies scholars, and Szymborska’s unique poetic style contributed to the immense interest in her work. The article discusses examples of Szymborska’s poetry permeating Italian popular culture, media, and public spaces, creating a large-scale literary and sociological phenomenon, as well as.